Optimization of infectious disease processes modelled by nonlinear delay differential equations - Savula, Y.; Shcherbatyi, M.; Shcherbata, H. (Фізико-математичне моделювання та інформаційні технології, 2010)
In this paper the numerical approach to the solution of optimization problems of processes which are modelled by nonlinear delay differential equations (DDEs) with constant delays is presented. Based on DDEs solution the different characteristics of the modelled process are calculated. One of them is selected as the objective functional. Other characteristics can play a role of constraints. The control is made by the functions, which define the coefficients of DDEs. As a result of piecewise-linear approximation of control function the non-linear mathematical programming problems are obtained. The efficiency of the software developed for solution of nonlinear DDEs and optimization of DDE systems is illustrated on the infectious disease process model.